Christian zionism as a factor of US politics - Jevtić Miroljub (Međunarodni Problemi)
One of the most important phenomena in US politics is Christian Zionism. The term Christian Zionism is related to unity of a large part of Protestant beliefs and the Zionists movement. The religious motives of US Protestants have coincided with the Jewish intention to go back to Palestine. In this way, Protestant religious motives could only be achieved by using political pressure on the US government. The goal of this pressure is to turn the foreign policy of Washington into a struggle for reconstruction and maintenance of the state of Israel. That is why many people wrongly believe that the US policy in Middle East is a product of the Jewish lobby. However, the US foreign policy in Middle East is a product of religious beliefs of Christian Zionists and the Jewish lobby is just using this fact for its own purposes. [Projekat Ministarstva nauke Republike Srbije, br. 179008]